PATHOPHYSIOLOGICAL MECHANISMS OF THYROID GLAND HORMONAL DYSREGULATION DURING EXPERIMENTAL THERMAL EXPOSURE - Tiron, O.I.; Vastyanov, R.S.; Shapovalov, V.Yu.; Yatsyna, O.I.; Kurtova, M.M. (World of Medicine and Biology, 2022)
The purpose of the study was to study the concentration of pituitary and iodine-containing hormones as well as hormones secreted by the parathyroid gland and the adrenal cortex in the dynamics of skin burns in rats under physiological 0.9 % NaCl solution administration. Blood plasma levels of thyroid-stimulating hormone, triiodothyronine, thyroxin, luteinizing hormone, follicle-stimulating hormone, aldosterone, corticosterone, testosterone and parathyroid hormone were determined 1, 3, 7, 14, 21 and 30 days after thermal skin burns in 138 white Wistar rats. The entire dysfunction of axis of hypothalamic-pituitary-thyroid regulation of a biological organism was established. A simultaneous secretory activity changes were shown in several functional regulatory axis – the pituitary-parathyroid gland, the pituitary-adrenal gland and the pituitary-gonads. Authors showed the primarily inhibition and disorganization of the morphological intraglandular organization in the initial time intervals after a skin burn and some spontaneous compensation after 7–14 days of the post-burn period was confirmed in a change of thyroid gland itself and other important endocrine elements secretory activity. NaCl administration is insufficient for therapeutic purposes and it is necessary to develop the effective pathogenetical scheme of thyroid gland functional state correction in skin burns.